BIAYA IKLAN, INTENSITAS PERSEDIAAN, PERTUMBUHAN PENJUALAN DAN TRANSAKSI PIHAK BERELASI PADA AGRESIVITAS PAJAK: ADVERTISING COSTS, INVENTORY INTENSITY, SALES GROWTH AND RELATED PARTY TRANSACTIONS ON TAX AGGRESSIVENESS - Resty, Sefrilia; Yusralaini, Yusralaini; Rusli, Rusli; Wahyuni, Nita (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
The research seeks to empirically investigate how Advertising Costs, Inventory Intensity, Sales Growth, and Related Party Transactions influence Tax Aggressiveness within the realm of Non-Cyclical Consumer Companies listed on the Indonesia Stock Exchange (IDX-IC Classification 2018-2022). The study targets non-cyclical sector consumer companies listed on the Indonesia Stock Exchange categorized under the IDX-IC classification from 2018 to 2022. The study utilised the multiple linear regression analysis approach to examine a sample of 15 organisations. The sample was picked via purposive selection and represented a total of 75 companies observed over a five-year period from 2018 to 2022. SPSS version 27 was utilized as the analytical tool. The research findings indicate that: (1) Advertising costs exert a significant influence on tax aggressiveness, evidenced by a significance level of 0.000 ≤ 0.05. (2) Inventory intensity also significantly impacts tax aggressiveness, as indicated by a significance level of 0.000 ≤ 0.05. (3) Sales growth, however, does not exhibit a significant effect on tax aggressiveness, with a significance level of 0.366 ≥ 0.05. (4) Similarly, related party transactions do not demonstrate a significant effect on tax aggressiveness, with a significance level of 0.109 ≥ 0.05.